The Role of the School Committee in Implementing the Anti-Bullying Program at SDIT Kaffah Islamic School - Izazy, Nurul Qolbi; Aldeia, A.M Saifullah; Martono, Sri Fajar; Manurung, Shiyamu; Ramadoni, Ramadoni (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
School bullying has become one of the major educational concerns across countries, including Indonesia, which has long-term negative consequences for the physical and mental health condition of the victims. Preventive and curative interventions can be taken by school to eliminate school bullying action, one of which is through implementing programmatic anti-bullying programs in schools. The anti-bullying program should be conducted collaboratively by involving parents and other stakeholders. This article aims to highlight the importance of parental involvement in preventing bullying behaviour in the school environment, particularly through the role of school committee. This study was conducted to examine how school committee of SDIT Kaffah Islamic School carrying out their role in regard of bullying prevention program in the school. Data collection was conducted through surveys, in-depth interviews, observations and document studies at SDIT Kaffah Islamic School. The results revealed that the school committee contributes to the anti-bullying program through their four main roles, namely providing advices to the school management, raising funds and resources to support anti-bullying program, supervising the implementation of anti-bullying program, and gathering suggestions, complaints, criticism from various education stakeholders. Based on the research findings, it is recommended that school committees should prioritize anti-bullying programs to ensure a supportive environment.